PENGARUH STRATEGI PEMASARAN TERHADAP MINAT KONSUMEN MEMBELI PRODUK PERUMAHAN (KASUS PADA PERUMAHAN SURYA MANDIRI TEROPONG PT. EFA ARTHA UTAMA) - Afdillah Firdaus; Endang Sutrisna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Marketing strategies is a set of n plan formulated by looking at the dimensions of the product, price, place and promotion to the goals and objectives, policies and rules that gives direction to the marketing efforts of companies from time to time, at each level, and reference and location, especially as the company's response in the face of competition environment and circumstances change. Consumer interest is growing for a motif based on the attributes in accordance with the wishes and needs in buying the product, based on these two companies should be appropriately designing marketing strategies to attract the interest of the consumers themselves to be interested in housing products offered so that when the consumer has berinat on products hence the decision to purchase such products will be created. This research was conducted in Housing Binoculars Surya Mandiri PT. Efa Artha Utama, Jalan Binoculars, Arengka-Pekanbaru. The purpose of this study was conducted to determine the influence of marketing strategies on growing consumer interest in housing PT. Efa Artha Utama, Jalan Binoculars, Arengka-Pekanbaru. In this research methodology is descriptive and quantitative with SPSS, where samples were used that consumers who buy housing PT. Efa Artha Utama, Jalan Binoculars, Arengka-Pekanbaru and as a resource that is led PT. Efa Artha Utama, Jalan Binoculars, Arengka-Pekanbaru. To determine the sample using data through interviews and questionnaires while the types and sources of data are primary and secondary data.From the results of data analysis include validity, reliability, simple linear regression, test of determination and t test the influence of marketing strategies which comprises four dimensions of the consumer interest is seen four dimensions. Each has indicator interrelated and positive influence on consumer interest in PT. Efa Artha Utama, Jalan Binoculars, Arengka-Pekanbaru.Keywords ; marketing strategies, consumer interest